Treatment Delay Impact on Overall Survival in Head and Neck Cancers - Habibullah, Asmatullah, Bashir Ahmad, Ahmad Shah, Nazeer Ahmad Sasoli, Muhammad Idrees Achakzai (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Head and Neck (HN) cancer is the commonly identified cancer across the globe and is considered as 8-10 % of all cancers in Southeast Asia. Early diagnosis and initiation of treatment are critical for increased survival rate among patients. Objective: To quantify the impact of treatment initiation time post diagnosis on the survival rate outcomes of patients suffering from with head and neck cancer. Study design: Retrospective cohort study Place and duration of study: Department of ENT Head & Neck Surgery, Bolan Medical College, Quetta from 1st May 2023 to 1st October 2023. Methodology: One hundred and ninety patients who were clinically diagnosed with head and neck cancers including squamous cell carcinoma of oral cavity, oropharynx, larynx, hypopharynx and under radiotherapy were enrolled. The included patients were. The patients were distributed into quartiles established on the time to start of treatment (0 to 27 days, 28 to 41 days, 42 to 60 days, and greater than 2 months). The validity of the time length between the start of treatment and diagnosis as well as impact on overall survival was investigated through multivariate cox proportional hazard regression model wherein greater than 2 month quartile served as a comparitive reference group. Results: The mean age of the patients was 61.35±9.5 years with majority being males. Each patient was followed on a mean of 56±10.3 months. There were 26.31% those patients who were actively tobacco users while 53.68% had quitted tobacco usage. The T staging presented 31.57% patient in T2 stage while 28.94% patients were in N0 staging. There were 33.15% patients having positive results for HPV status. The most frequent treatment applied was concurrent chemoradiotherapy for cervical cancer (CCRT) of 57.36% patients. There was insignificant variance within the time of initiation of treatment with 26.84% of patients having the treatment initiated within 0 to 27 days of diagnosis. Kaplan Meier overall survival observed that those patients whose treatment was initiated within 42-60 days had most promising survival rate. Therefore, the overall survival time of the patients was not significantly different between 0-27 and 28- 41 days group in comparison to 60 days group. While the survival of patients within the 42 to 60 days group significantly higher than other groups (p vale 0.011). The similar findings were observed when the treatment initiation groups were compared for Cox proportional hazard ratio against age adjusted model and multivariant model. Conclusion: For some patients the delay in treatment time (42-60 days) may not affect the survival rate negatively rather this time may be appropriately used for proper planning treatment Substantial delay in treatment can lead to a negative impact on survival rate. Keywords: Treatment delay, Head & neck cancer, Survival rate